Study on the Preparation and Properties of Lubricating and Anti-Corrosion Seal Coating on the Chromium-Free Dacromet Coating Surface - LI Qing-peng, ZHANG Deng-hua, YANG Hong-qiang, WANG Na, KONG Xiang-feng, GUAN-yong, LIU Jian-guo, YAN Chuan-wei, ZHANG Liang, YIN Yue-jun, HAN Chang-zhi (Cailiao Baohu)
In order to improve the lubricating and anti-corrosion performance of the chromium-free Dacromet coating, a water-based chromium-free lubricating seal coating applied on the surface of the chromium-free Dacromet coating was prepared with using flake Al powder as filler, PTFE as lubricating filler and silane A-187 as film forming material.Subsequently, the surface morphology, composition and corrosion resistance of the coatings were investigated by scanning electron microscopy(SEM), energy dispersive spectrometer(EDS), neutral salt spray test, potentiodynamic polarization curve test and EIS analysis.Results showed that the water-based chromium-free lubricating seal coating was well combined with the chromium-free Dacromet coating, and the coating surface after painting became smoother and more compact.Moreover, there were no obvious red rust formed on the surface of the composite coating(chromium-free Dacromet coating plus water based chromium-free lubricating sealing coating)after 960 h salt spray test.In the comparation of single chromium-free Dacromet coating, the composite coating possessed more positive corrosion potential, lower corrosion current and larger corrosion resistance, indicating that the composite coating had better anti-corrosion performance.